Pathological worry in hypertensive compared to normotensive population in Michoacan (Mexico) - Velázquez Díaz, Marcela; Espinoza González, Fernando; Martínez Medina, María Patricia; Padrós Blázquez, Ferran (Acta Universitaria, 2016)
Diverse studies have reported high anxiety levels as a main factor associated with hypertension. However, there are few studies showing the possible relationship between pathological worry and hypertension; hence it is the main focus of this study. Sample size consists of 306 male and female participants (n = 153 hypertensive and n = 153 normotensive), who were paired according to sex, age, marital status, and education level.  Penn State Worry Questionnaire, Beck Anxiety Inventory and Beck Depression Inventory were applied in both groups. Results indicate higher levels of pathological worry, anxiety and depressive symptoms (all with p < 0.001) in the hypertensive group. The main limitation of our study is that the type of treatment administered to our sample was not controlled, nor the possible side effects. However, our results suggest that the intervention on pathological worry could be beneficial for hypertensive patients.
Keywords: Array; Array; Array; Array; Array